Association of short‐term exposure to ambient air pollution with mortality from ischemic and hemorrhagic stroke. (11th April 2022) - Xu, Ruijun; Wang, Qingqing; Wei, Jing; Lu, Wenfeng; Wang, Rui; Liu, Tingting; Wang, Yaqi; Fan, Zhaoyu; Li, Yingxin; Xu, Luxi; Shi, Chunxiang; Li, Guo; et al.
Abstract: Background: Short‐term exposure to ambient air pollution has been linked to increased risk of stroke mortality, but its adverse effects on mortality from specific types of stroke including ischemic stroke and hemorrhagic stroke remain poorly understood. Methods: Using the China National Mortality Surveillance System, we conducted a time‐stratified case‐crossover study among 412, 567 stroke deaths in Jiangsu province, China during 2015–2019. Residential daily PM2.5, PM10, SO2, NO2, CO, and O3 exposure concentrations were extracted from the ChinaHighAirPollutants dataset for each subject. Conditional logistic regression models were performed to conduct exposure–response analyses. Results: Each 10 μg/m 3 increase of PM2.5, PM10, SO2, NO2, CO, and O3 was respectively associated with a 1.44%, 0.93%, 5.55%, 2.90%, 0.148%, and 0.54% increase in odds of mortality from ischemic stroke, which was significantly stronger than that from hemorrhagic stroke (percent change in odds: 0.74%, 0.51%, 3.11%, 1.15%, 0.090%, and 0.10%). The excess fraction of ischemic stroke mortality associated with PM2.5, PM10, SO2, NO2, CO, and O3 exposure was 6.90%, 6.48%, 8.21%, 8.61%, 9.67%, and 4.76%, respectively, which was also significantly higher than that of hemorrhagic stroke mortality (excess fraction: 3.49%, 3.48%, 4.69%, 3.48%, 5.86%, and 0.88%). These differences in adverse effects generally remained across sex, age, and season. Conclusions: Short‐term exposure to ambient air pollution was significantly associated with increased risk of both ischemic and hemorrhagic stroke mortality and posed considerable excess mortality. Our results suggest that air pollution exposure may lead to substantially greater adverse effects on mortality from ischemic stroke than that from hemorrhagic stroke. Abstract : Short‐term exposure to ambient air pollution was significantly associated with increased risk of both ischemic and hemorrhagic stroke mortality and posed considerable excess mortality. Our findings suggest that ambient air pollution may lead to substantially greater adverse effects on mortality from ischemic stroke than that from hemorrhagic stroke.